Syariah Index and Portfolia Index: Evidence from Cointegration - Masron, T. A.; Abd Wahab, A. (Universiti Sains Islam Malaysia, 2024)
The main objective of this study is to identify the nature of the relationship between the Syariah index and portfolio investment. Using the cointegration procedure, a long run steady state relationship between the Syariah index and portfolio invstment is established. We found a unilateral Granger causality where the inward of portfolio investment Granger causes Syariah index, but Syariah index does not Granger cause portfolio investment. Additionally, the results from the impulse response function show that the impact of shock in Syariah index to portfolio investment is dominant, while the reverse causality is considered negligible or minimal.